A cluster approach to the analysis of experimental data of the NEVOD-EAS shower array. (November 2019) - Shulzhenko, I A; Ardashev, V A; Chiavassa, A; Dobrynchuk, L V; Gromushkin, D M; Likiy, O I
Abstract: The NEVOD-EAS array for the detection of extensive air showers in the energy range 10 15 –10 17 eV is being created in MEPhI on the basis of the Experimental complex NEVOD. The array will allow independent estimations of the size, axis position and arrival direction of EAS registered by the detectors of the experimental complex. The NEVOD-EAS registering system is organized in a cluster principle, and data analysis is performed using a newly developed cluster approach. The features of this approach to the NEVOD-EAS experimental data analysis are discussed.